The evolution, facilitators, barriers, and additional activities of acute flaccid paralysis surveillance platform in polio eradication programme Bangladesh: a mixed-method study - Humayra Binte Anwar; Yameen Mazumder; Sanjana Nujhat; Bushra Zarin Islam; Anna Kalbarczyk; Olakunle Alonge; Malabika Sarker (Taylor & Francis Group, 2024)
Background The Global Polio Eradication Initiative (GPEI) helped develop the standard acute flaccid paralysis surveillance (AFP) system worldwide, including, knowledge, expertise, technical assistance, and trained personnel. AFP surveillance can complement any disease surveillance system. Objective This study outlines AFP surveillance evolution in Bangladesh, its success and challenging factors, and its potential to facilitate other health goals. Methods This mixed-method study includes a grey literature review, survey, and key informant interviews (KIIs). We collected grey literature from online websites and paper documentation from GPEI stakeholders. Online and in-person surveys were conducted in six divisions of Bangladesh, including Dhaka, Rajshahi, Rangpur, Chittagong, Sylhet, and Khulna, to map tacit knowledge ideas, approaches, and experiences. We also conducted KIIs, and Data were then combined on focused emerging themes, including the history, challenges, and successes of AFP surveillance programme. Results According to the grey literature review, survey, and KII, AFP surveillance successfully contributed to decreasing polio in Bangladesh. The major facilitating factors were multi-sectoral collaboration, Surveillance Immunization Medical Officer (SIMO) network activities, social environment, community-based surveillance, and promising political commitment. On the other hand, high population growth, hard-to-reach areas, people residing in risky zones, and polio transition planning were significant challenges. Bangladesh is also utilizing these polio surveillance assets for other vaccine-preventable diseases. Conclusion As the world is so close to eradicating polio, the knowledge, and other assets of the AFP surveillance, could be used for other health programmes. In addition, its strengths can be leveraged for combating new and emerging diseases.